Antibody–Drug Conjugates as Cancer Therapeutics: Past, Present, and Future. (October 2017) - Vezina, Heather E.; Cotreau, Monette; Han, Tae H.; Gupta, Manish
Abstract: Antibody–drug conjugates (ADCs) represent an innovative therapeutic approach that provides novel treatment options and hope for patients with cancer. By coupling monoclonal antibodies (mAbs) to cytotoxic small‐molecule payloads with a plasma‐stable linker, ADCs offer the potential for increased drug specificity and fewer off‐target effects than systemic chemotherapy. As evidence for the potential of these therapies, many new ADCs are in various stages of clinical development. Because their structure poses unique challenges to pharmacokinetic and pharmacodynamic characterization, it is critical to recognize the differences between ADCs and conventional chemotherapy in the design of ADC clinical development strategies. Although some properties may be determined mainly by either the mAb or the small‐molecule portion, the behavior of these agents is not always predictable. Furthermore, because the absorption, distribution, metabolism, and excretion (ADME) of ADCs are influenced by all 3 of its components (mAb, linker, and payload), it is important to characterize the intact molecule, any target‐mediated catabolic clearance of the mAb, and the ADME properties of the small‐molecule payload. Here we describe key issues in the clinical development of ADCs, including considerations for designing first‐in‐human studies for ADCs. We discuss some difficulties of ADC pharmacokinetic characterization and current approaches to overcoming these challenges. Finally, we consider all aspects of clinical pharmacology assessment required during drug development, using examples from the literature to illustrate the discussion.